Current concerns and perspectives on Zika virus co-infection with arboviruses and HIV. (May 2018) - Rothan, Hussin A.; Bidokhti, Mehdi R.M.; Byrareddy, Siddappa N.
Abstract: Dissemination of vector-borne viruses, such as Zika virus (ZIKV), in tropical and sub-tropical regions has a complicated impact on the immunopathogenesis of other endemic viruses such as dengue virus (DENV), chikungunya virus (CHIKV) and human immunodeficiency virus (HIV). The consequences of the possible co-infections with these viruses have specifically shown significant impact on the treatment and vaccination strategies. ZIKV is a mosquito-borne flavivirus from African and Asian lineages that causes neurological complications in infected humans. Many of DENV and CHIKV endemic regions have been experiencing outbreaks of ZIKV infection. Intriguingly, the mosquitoes, Aedes Aegypti and Aedes Albopictus, can simultaneously transmit all the combinations of ZIKV, DENV, and CHIKV to the humans. The co-circulation of these viruses leads to a complicated immune response due to the pre-existence or co-existence of ZIKV infection with DENV and CHIKV infections. The non-vector transmission of ZIKV, especially, via sexual intercourse and placenta represents an additional burden that may hander the treatment strategies of other sexually transmitted diseases such as HIV. Collectively, ZIKV co-circulation and co-infection with other viruses have inevitable impact on the host immune response, diagnosis techniques, and vaccine development strategies for the control of these co-infections. Highlights: Rise of ZIKV co-infection with vector-borne viruses in overlapping endemic areas. Studying control and prevention strategies for ZIKV, other flaviviruses and HIV. Consideration of HIV/ZIKV transmission in vaccine development. Effective control of ZIKV transmission using Wolbachia against Aedes mosquitos. Development of ZIKV vaccines need to consider of co-infection with human pathogens.